2023
DOI: 10.3390/ani13233602
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Reduces ROS by Increasing GSH in Vitrified Sheep Embryos

Andrea Carolina González-Garzón,
Julio Porfirio Ramón-Ugalde,
Demetrio Alonso Ambríz-García
et al.

Abstract: The in vitro production and cryopreservation of mammalian embryos generates reactive oxygen species (ROS) due to conditions of the system that can overcome their antioxidant protection. Resveratrol is an antioxidant used in in vitro systems to improve blastocyst rates, but its effect on antioxidant enzymes such as glutathione (GSH) in embryos produced by in vitro fertilization (IVF) after vitrification has not been reported. The objective of this study was to evaluate the effects of resveratrol on the in vitro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Oocyte vitrification is increasingly used for female fertility preservation. However, as previously described, vitrification may cause damage to the endogenous antioxidant system and redox homeostasis imbalance in several mammalian oocytes [ 57 65 ], which puts a great adverse impact on the developmental potential of the oocyte [ 21 , 58 60 ]. In the present study, we found that the PA zygotes derived from vitrified mouse MII oocytes showed the increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Oocyte vitrification is increasingly used for female fertility preservation. However, as previously described, vitrification may cause damage to the endogenous antioxidant system and redox homeostasis imbalance in several mammalian oocytes [ 57 65 ], which puts a great adverse impact on the developmental potential of the oocyte [ 21 , 58 60 ]. In the present study, we found that the PA zygotes derived from vitrified mouse MII oocytes showed the increased oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The level of ROS production in the sperm was evaluated by a fluorescent probe with 2,7-dichlorodi-hydrofluorescein diacetate (DCFH-DA, Beyotime, Shanghai, China) [ 24 ]. Briefly, the thawed semen was diluted in basic diluent (1:6) and 50 µL of samples were mixed with DCFH-DA (10 mM).…”
Section: Methodsmentioning
confidence: 99%